Analisis Struktur, Perilaku, dan Kinerja Pasar Jeruk Siam di Kota Batu - Swasono, Agustinus Setyo; Relawati, Rahayu; Ningsih, Gumoyo Mumpuni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The context of the structure, market behavior, and performance of the Siamese citrus market in Batu City, which is one of the citrus producing areas, will have a significant influence on the formation of Siamese orange prices in Batu City. This study analyzes the market structure, market behavior, and market performance in Siamese oranges which have the potential to be one of the shapers of Siamese prices that will determine the price of Siamese oranges and the income that will be received by farmers. The purpose of this study is to (1) know and analyze the structure of the Siamese citrus market (2) know and analyze the behavior of the Siamese citrus market (3) know and analyze the performance of the Siamese market in Batu City. The method used in this study is a survey, with a sampling technique using snowball sampling. Data analysis was carried out in a quantitative descriptive way. The results of the research show that: (1) qualitatively, the market structure is included in the market of perfect competition; (2) market behavior shows two marketing channels, namely Marketing Channel I (farmers-middlemen-wholesalers-retailers) and Marketing Channel II (farmers-middlemen-retailers); and (3) the most profitable marketing performance was found on Marketing Channel II.